Case series: Pyramidal cataracts, intact irides and nystagmus from three novel PAX6 mutations - Bharesh K. Chauhan; Anagha Medsinge; Matthew P. Baumgartner; Hannah L. Scanga; Smaragda Kamakari; Eva Gajdosova; Carlos J. Camacho; Ken K. Nischal (American Journal of Ophthalmology Case Reports, 2018)
Purpose: To investigate the association between novel PAX6 mutations to bilateral anterior pyramidal congenital cataracts (APyC), complete and intact irides, and nystagmus. Observations: This is a retrospective observational case series in a multi-center setting with genetic testing. Three female patients were diagnosed with bilateral APyC, intact irides and nystagmus. Genetic testing identified the three patients had novel missense mutations in PAX6 – c.128C > T; p.Ser43Phe (S43F), c. 197T > A; p.Ile66Asn (I66N) and c.781C > G; p.Arg261Gly (R261G). Conclusions and importance: This study demonstrates a novel phenotype of bilateral APyC, intact irides, and nystagmus in whom genetic testing for PAX6 identified novel missense mutations (S43F, I66N, R261G) in highly conserved DNA-binding domains. Implications of understanding why the iris is present in these cases is discussed. Keywords: Pyramidal cataracts, Intact irides, Nystagmus, Novel PAX6 missense mutations